Development of Massive Open Online Learning Environments to Promote Self-directed Learning based on Constructivist Approach - Duangnim, Anupap; Napapongs, Wichai; Kaosaiyaporn, Ophat; Tansakul, Jirawat; Inkaew, Chamaiporn (Journal of Information and Learning [JIL], 2022)
The purposes of this research were: 1) to develop massive open online learning environments, 2) to compare learner’s pre-test and post-test performance, and 3) to investigate learners’ satisfaction. The sample group were 45 students enrolling in Research in Educational Technology and Communications courses with at least 70 percent academic achievement. The following were the research tools: 1) lesson plan, 2) lesson material, 3) Massive Open Online Course, 4) an achievement exam, and 5) a satisfaction survey. The data were analyzed using descriptive statistics including mean, standard deviation and t-test dependent. The results revealed that: 1) the development of the Massive Open Online Learning was of the highest quality, 2) the learner’s post-test scores of learning achievement were significantly higher than their pre-test scores at the .01 level of significance, and 3) the results of the learner satisfaction study were at the highest level.